Cher : singer and actress - Petrucelli, Rita, 1942-; Lazzarino, Luciano (Vero Beach, Fla. : Rourke Enterprises, 1989)
Presents a biography of the famous singer and actress who won an Academy Award in 1988. Includes information on setting goals.
3.9
K-3
Keywords: Cher, -- 1946- -- Juvenile literature; Cher, -- 1946-; Cher, -- 1946-; Singers -- United States -- Biography -- Juvenile literature; Motion picture actors and actresses -- United States -- Biography -- Juvenile literature; Singers; Actors and actresses; Singers -- Biography; Actors -- Biography; Singers -- Biography; Actors and actresses -- Biography